Genetic diversity analysis of Ghurrah pig based on microsatellite markers - BORO, PRASANTA; PATEL, B H M; SAHOO, NIHAR RANJAN; GAUR, G K; DUTT, TRIVENI; SINGH, MUKESH; NAHA, B C (The Indian Journal of Animal Sciences, 2019)
For analysis of genetic variation within Ghurrah, the local pigs of Rohilkhand region was explored using 16 FAOISAG microsatellite markers with 40 genetically unrelated pigs from the native breeding tract. Genomic DNA was isolated and amplified with microsatellite primers labeled with fluorescent dyes and genotyped using genetic analyser. The estimates of various genetic diversity parameters revealed mean number of observed alleles (Na), effective number of alleles (Ne), observed (Ho) and expected (He) heterozygosity values, polymorphic information content (PIC) and F-values to be 8.5±0.99, 4.78±0.57, 0.47±0.04 and 0.74±0.05, 0.74±0.04 and 0.38±0.03, respectively. The high PIC value suggested that all the microsatellite markers were highly polymorphic and suitable for molecular characterization of this pig. There was substantial genetic variation and polymorphism across the studied loci. There was absence of genetic bottleneck in the studied population. The medium inbreeding coefficient indicates a need to formulate the appropriate breeding strategies to enhance heterozygosity in the population.